Fundamentals of Surgical Simulation Principles and Practice - Gallagher, Anthony G.; O'Sullivan, Gerald C.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
Fundamentals of Surgical Simulation explains in detail, from a behavioural science/human factors perspective, why modern image guided medicine such as surgery, interventional cardiology and interventional radiology are difficult to learn and practice. Medicine is currently at a tipping point in terms of how physicians in procedural based medicine are trained. Fundamentals of Surgical Simulation helps drive this change and is a valuable resource for medical trainers and trainees alike. For trainers, this book gives explicit theoretical and applied information on how this new training paradigm works thus allowing them to tailor the application of simulation training to their program, no matter where in the world they work. For the trainee, it allows them to see and understand the rules of this new training paradigm thus allowing them to optimize their approach to training and reaching proficiency in as efficient a manner as possible. For the simulation researcher, engineer and medical profession Fundamentals of Surgical Simulation poses some difficult questions that require urgent unambiguous and agreed answers.
Agents of change -- Simulations for procedural training -- Human factors in acquiring medical skills; Perception and Cognition -- Human factors in acquiring medical skills; Learning and skill acquisition in procedural medicine -- Metrics for the measurement of skill -- Metric based simulation training -- Validation of metrics coupled to simulation training -- Metric-based training to proficiency; What is it and how is it done? -- Didactic education and training for improved intra-operative performance; e-learning comes of age -- Simulation training for improved procedural performance -- Simulation in and for medicine; Where next? -- Proficiency-based progression simulation training; a to-do list for medicine.
Keywords: Medicine; Emergency medicine; Medicine & Public Health; Emergency Medicine; Medicine/Public Health, general